The Comparability of Pt to Pt‐Ru in Catalyzing the Hydrogen Oxidation Reaction for Alkaline Polymer Electrolyte Fuel Cells Operated at 80 °C - Li, Qihao; Peng, Hanqing; Wang, Yingming; Xiao, Li; Lu, Juntao; Zhuang, Lin (Angewandte Chemie International Edition, 2019)
The Pt‐catalyzed hydrogen oxidation reaction (HOR) for alkaline polymer electrolyte fuel cells (APEFCs) has been one of the focus subjects in current fuel‐cell research. The Pt catalyst is inferior for HOR in alkaline solutions, and alloying with Ru is an effective promotion strategy. APEFCs with Pt‐Ru anodes have provided a performance benchmark over 1 W cm−2 at 60 °C. The Pt anode is now found to be in fact as good as the Pt‐Ru anode for APEFCs operated at elevated conditions. At 80 °C with appropriate gas back‐pressure, the cell with a Pt anode exhibits a peak power density of about 1.9 W cm−2, which is very close to that with a Pt‐Ru anode. Even by decreasing the anode Pt loading to 0.1 mg cm−2, over 1.5 W cm−2 can still be achieved at 80 °C. This finding alters the previous understanding about the Pt catalyzed HOR in alkaline media and casts a new light on the development of practical and high‐power APFEC technology. Alkaline polymer electrolyte fuel cells (APEFCs) with Pt‐Ru anodes have provided a performance benchmark over 1 W cm−2 at 60 °C. The Pt anode (gray) is now found to be as good as the Pt‐Ru anode (red) for APEFCs operated at elevated conditions. At T=80 °C with appropriate gas back‐pressure p, the cell with a Pt anode exhibits a peak power density of about 1.9 W cm−2, which is very close to that with a Pt‐Ru anode.